Existence of the Indigenous Community Ammatoa Kajang - Sartika Sartika; Syamsu A Kamaruddin; Arlin Adam; Andi Ihsan; Ansyaruddin Samad (Universitas Muhammadiyah Palu, 2024)
The aim of this research is to determine the existence of the Ammatoa indigenous community within the Kajang society and to identify the factors influencing the existence of the Ammatoa indigenous community within Kajang. The method employed in this research is descriptive method involving observation, interviews, and documentation. The results of this research indicate that in the life of the Ammatoa indigenous community in Tana Toa Village, there are several aspects demonstrating the existence of the Ammatoa indigenous community, namely economic, legal, educational, and cultural aspects within the community. Furthermore, the factors influencing the existence of the Ammatoa indigenous community within Kajang include adaptation factors, goal achievement factors, integration factors, and norm/value factors. The presence of the Ammatoa indigenous community is inseparable from their beliefs, as evidenced by the principle of tallasa kamase-masea (simple living) embodied in the pasang ri kajang. The Ammatoa indigenous community upholds all forms of tradition that have existed since ancient times.